Stylistic Features of Tangis Dilo in the Southeast Aceh Wedding Ceremony - Sri Rahayu; Sagala, Rakhmat Wahyudin (Journal of General Education Science, 2022)
This study deals with figurative language analysis on Tangis Dilo Suku Alas Wedding Ceremony: A Semantics Analysis. It aimed to uncover the figurative language types in Tangis Dilo wedding ceremonies. The data were taken from Tangis Dilo lyrics performed by the participants during the wedding ceremony. The descriptive qualitative method was applied to analyze the data. The finding reveals that there were 62 figurative languages on Tangis Dilo. The result includes personification 19, simile 14, metaphor 6, hyperbole 11, litotes 5, metonymy 3, and Irony 4. The figurative language most dominantly used on Tangis Dilo was personification 19.